A Series of Analogues to the AT2R Prototype Antagonist C38 Allow Fine Tuning of the Previously Reported Antagonist Binding Mode. Issue 1 (24th January 2019) - Isaksson, Rebecka; Lindman, Jens; Wannberg, Johan; Sallander, Jessica; Backlund, Maria; Baraldi, Dhaniel; Widdop, Robert; Hallberg, Mathias; Åqvist, Johan; Gutierrez de Teran, Hugo; Gising, Johan; Larhed, Mats
Abstract: We here report on our continued studies of ligands binding to the promising drug target angiotensin II type 2 receptor (AT2 R). Two series of compounds were synthesized and investigated. The first series explored the effects of adding small substituents to the phenyl ring of the known selective nonpeptide AT2 R antagonistC38, generating small but significant shifts in AT2 R affinity. One compound in the first series was equipotent toC38 and showed similar kinetic solubility, and stability in both human and mouse liver microsomes. The second series was comprised of new bicyclic derivatives, amongst which one ligand exhibited a five‐fold improved affinity to AT2 R as compared toC38 . The majority of the compounds in the second series, including the most potent ligand, were inferior toC38 with regard to stability in both human and mouse microsomes. In contrast to our previously reported findings, ligands with shorter carbamate alkyl chains only demonstrated slightly improved stability in microsomes. Based on data presented herein, a more adequate, tentative model of the binding modes of ligand analogues to the prototype AT2 R antagonistC38 is proposed, as deduced from docking redefined by molecular dynamic simulations. Abstract : Time to tune in : Continued exploration of the structure–activity relationship of AT2 R prototype antagonistC38 generate ligands of similar affinity, which enable the fine tuning of a proposed binding mode. A new head group is also explored, showing promising improvement in affinity, but did not display a similar improvement of stability in liver microsomes.